LTCP improving the performance of TCP in highspeed networks. - Bhandarkar, Sumitha
In this paper, we propose Layered TCP (LTCP for short), a set of simple modifications to the congestion window response of TCP to make it more scalable in highspeed networks. LTCP modifies the TCP flow to behave as a collection of virtual flows to achieve more efficient bandwidth probing. The number of virtual flows emulated is determined based on the dynamic network conditions by using the concept of virtual layers, such that the convergence properties and RTT-unfairness behavior is maintained similar to that of TCP. In this paper, we provide the intuition and the design for the LTCP protocol modifications and evaluation results based on ns-2 simulations and Linux implementation. Our results show that LTCP has promising convergence properties, is about an order of magnitude faster than TCP in utilizing high bandwidth links, employs few parameters and retains AIMD characteristics
Keywords: Computer systems organization; Computer communication networks; Network protocols; Design; Experimentation; Theory